Is resource specialization the key?: some, but not all Red Crossbill call types associate with their key conifers in a diverse North American landscape - Centanni, Caleb; Robinson, W. Douglas; Young, Matthew A. (Frontiers in Bird Science, 2024)
Red Crossbills (Fringillidae: Loxia curvirostra) are finches specialized to pry open cones and extract seeds of coniferous trees. Within the species, variable bill morphology may provide more efficient foraging on some species of conifers than others. Subgroups also have distinctly different contact calls often given in flight (hereafter, call types). Variable morphology and discrete call types suggest the existence of distinct evolutionary lineages. Because coniferous trees produce seeds on irregular and unpredictable schedules, crossbills wander widely in search of food. The key conifer hypothesis suggests that each call type diverged by specializing on a single conifer species to maximize foraging efficiency, while other hypotheses have emphasized geographic isolation as a driver of lineage divergence. To quantify the degree to which call types occur with specific conifer species, we surveyed Red Crossbills in five ecoregions of western and central Oregon, USA, an area with high conifer diversity. Two of five call types (Types 5 and 10) were encountered in only one ecoregion and associated with their hypothesized key conifers. Three others (Types 2, 3, and 4) were found to wander widely and did not exclusively align geographically with their presumed key conifer species. Whereas types 2 and 3 were sometimes associated with their proposed key conifers, they wandered widely during our 2-year study and occurred with a wide variety of conifers. Type 4 was not significantly associated with its key conifer and also wandered widely during our study. Relationships of call types with key conifers were weaker in the winter and spring, when Types 3 and 4 were frequently encountered in hard-coned pines rather than their soft-coned key conifer species. In our study area, the key conifer hypothesis was strongly supported only for call type 10 as that call type was not encountered away from the coastal range of Sitka Spruce (Picea sitchensis). We found mixed support for the key conifer hypothesis based on our measure of geographic associations of crossbills with a diverse array of coniferous tree species. In most cases we observed, crossbills wandered widely and associated with multiple species of conifers.